Factors Associated With Community Based Health Insurance Healthcare Service Utilization of Households in South Gondar Zone, Amhara, Ethiopia. A Community-Based Cross-Sectional Study. (May 2022) - Moyehodie, Yikeber Abebaw; Fenta, Setegn Muche; Mulugeta, Solomon Sisay; Agegn, Setegn Bayabil; Yismaw, Embet; Biresaw, Hailegebrael Birhan; Muluneh, Mitiku Wale; Masresha, Bezanesh Melese; Dagnaw, Fentaw Teshome
In Ethiopia, community-based health insurance was implemented to promote equitable access to sustainable quality health care and increase financial protection. The purpose of this study was to identify factors associated with community-based Health Insurance, Health Care Service Utilization of Households in the South Gondar Zone. A community-based cross-sectional study was employed. Data were collected among 619 randomly selected households in the south Gondar zone. Chi-square and binary logistic regression analyses with a P -Value of less than .05 were used to determine the association. Out of the total households, 511(82.6%) were using the CBHI scheme for health care service utilization. Residence, marital status, education level, occupation status, family size, presence of under-five children in the household, presence of elders in the households, nearest health institution, presence of chronic illness in the household's, time taken to reach health institution, an attitude of a household were the determinant factors of community-based health insurance scheme health care service utilization of households. It is recommended that the local, regional and national governments, policymakers on optimal actions, NGOs, and other supporting organizations shall improve or scale-up the scheme by providing awareness to the community based on these significant factors and the attitude of households.